2019
DOI: 10.3390/foods8100505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed Electric Field-Assisted Osmotic Dehydration and Edible Coating on the Recovery of Anthocyanins from In Vitro Digested Berries

Abstract: Berry fruits, such as strawberries and blueberries, are rich sources of anthocyanins. Several studies have been made on the impact of non-thermal treatments on safety, shelf-life and nutritional characteristics of such products, but the effects of these processes on anthocyanin stability during digestion in the gastrointestinal tract are still not completely clear. The aim of this study was to assess the recovery of anthocyanins after simulated gastrointestinal digestion of (1) strawberry samples, pre-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The degradation of anthocyanins was concurrent with an increase in protocatechuic acid (88.6 mg kg −1 ), coumaric acid (85.7 mg kg −1 ), and ferulic acid (73.5 mg kg −1 ), in the intestinal fraction, which resulted in an increase in their bioaccessibility in this study. The application of encapsulation techniques could protect the anthocyanins from degradation in the small intestine [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of anthocyanins was concurrent with an increase in protocatechuic acid (88.6 mg kg −1 ), coumaric acid (85.7 mg kg −1 ), and ferulic acid (73.5 mg kg −1 ), in the intestinal fraction, which resulted in an increase in their bioaccessibility in this study. The application of encapsulation techniques could protect the anthocyanins from degradation in the small intestine [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although anthocyanin recovery was in general very low after in vitro digestion, the digested extracts of strawberry showed the highest protective effect compared to the extracts from other berries. In a previous study we also showed a low recovery of cyanidin-3 -O- glucoside and malvidin-3 -O- glucoside after in vitro digestion of strawberry and blueberry, respectively [ 44 ]. Garcia et al [ 21 ] also reported that only 19.3% of total phenols were recovered after in vitro GI digestion of raspberry, while most phytochemicals present in the original extracts suffered substantial modification after digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers observed its decline as a result of heat treatment (caused by its degradation), as observed in unsweetened snacks A and B and in snack A with the addition of trehalose (A_t). Increased content of flavonoids in fruit bars with addition of trehalose may indicate that trehalose preserved lipid bilayers during dehydration, and thus protected some bioactive compounds [ 36 ]. Moreover, notable differences in flavonoid content among analyzed kiwifruit snacks could occur for the unstable behavior of flavonoids during storage.…”
Section: Discussionmentioning
confidence: 99%